Agricultural productivity and the sectoral reallocation of labor in rural India - Emerick, Kyle (Journal of development economics, 2018)
How do shocks to agricultural productivity affect the allocation of labor across sectors of the economy? To answer this, I use data from rural India to show that exogenous increases in agricultural productivity — caused by abnormally high levels of precipitation — lead to an increase in the labor share of the non-agricultural sector. I further show that the non-tradable sector expands significantly when agricultural output increases. This evidence is consistent with increasing agricultural output causing increased demand for local non-tradables, which in turn increases the non-agricultural labor share. •Short-term increases in agricultural productivity in India cause labor to shift to the non-agricultural sector.•Consistent with local demand effects, local non-tradable sectors absorb much of the labor that leaves agriculture.•The effects are largest for more educated and higher caste households.